Pilot Study of the Efficacy and Safety of Nail Gel Containing Artemisia abrotanum Extract and Glycerin in the Treatment of Nail Plate Surface Abnormality - Supenya Varothai; Sumanas Bunyaratavej; Charussri Leeyaphan; Sutasinee Phaitoonwattanakij; Waranaree Winayanuwattikun; Kanyalak Munprom (Siriraj Medical Journal, 2021)
Background: Nail gels are utilized for the treatment of nails for nail plate surface abnormalities. However, the objective measurement of nail gel treatment is limited. Objective: This study investigated the efficacy and safety of a nail gel containing glycerin and Artemisia abrotanum extract in treating nail plate surface abnormalities. Material and Methods: All nails were evaluated with a Visiometer® system and by transonychial water loss (TOWL) at baseline, and at the 2nd and 8th weeks of treatment. Results: In total, 19 patients with a mean age of 50.6 years old were enrolled and 50 nails were studied. Sixty percent of the patients showed significant clinical improvement, as determined by the total agreement between two treatment-blinded dermatologists. Regarding the Visiometer®, a significant reduction in the SER value (roughness) of the nail plates was found at the 2nd week, while at the 8th week, the surface and volume values had significantly decreased from baseline and also from the values at the 2nd week. There was a significant improvement in the Rku (smoothness) value at the 8th week compared to baseline. The mean TOWL at the 2nd and 8th weeks were statistically decreased from baseline. No side effects were detected. Conclusions: This nail gel containing Artemisia abrotanum extract provided benefits in restoring hydration and improving the nail barrier in patients with nail surface abnormalities.